Necrosectomy versus stand-alone suboccipital decompressive craniectomy for the management of space-occupying cerebellar infarctions - a retrospective multicenter study - Hernandez Duran, Silvia; Walter, Johannes; Behmanesh, Bedjan; Bernstock, Joshua D.; Czabanka, Marcus; Dinc, Nazife; Dubinski, Daniel; Freiman, Thomas M.; Günther, Albrecht; Hellmuth, Kara; Herrmann, Eva; Konczalla, Juergen; et al. (Neurosurgery, 2024)
BACKGROUND AND OBJECTIVES: - Space-occupying cerebellar stroke (SOCS) when coupled with neurological deterioration represents a neurosurgical emergency. Although current evidence supports surgical intervention in such patients with SOCS and rapid neurological deterioration, the optimal surgical methods/techniques to be applied remain a matter of debate. - METHODS: - We conducted a retrospective, multicenter study of patients undergoing surgery for SOCS. Patients were stratified according to the type of surgery as (1) suboccipital decompressive craniectomy (SDC) or (2) suboccipital craniotomy with concurrent necrosectomy. The primary end point examined was functional outcome using the modified Rankin Scale (mRS) at discharge and at 3 months (mRS 0-3 defined as favorable and mRS 4-6 as unfavorable outcome). Secondary end points included the analysis of in-house postoperative complications, mortality, and length of hospitalization. - RESULTS: - Ninety-two patients were included in the final analysis: 49 underwent necrosectomy and 43 underwent SDC. Those with necrosectomy displayed significantly higher rate of favorable outcome at discharge as compared with those who underwent SDC alone: 65.3% vs 27.9%, respectively (P < .001, odds ratios 4.9, 95% CI 2.0-11.8). This difference was also observed at 3 months: 65.3% vs 41.7% (P = .030, odds ratios 2.7, 95% CI 1.1-6.7). No significant differences were observed in mortality and/or postoperative complications, such as hemorrhagic transformation, infection, and/or the development of cerebrospinal fluid leaks/fistulas. - CONCLUSION: - In the setting of SOCS, patients treated with necrosectomy displayed better functional outcomes than those patients who underwent SDC alone. Ultimately, prospective, randomized studies will be needed to confirm this finding.
Gesehen am 01.08.2024